Validation of a Gymnastic Functional Measurement Tool in Technical Skill Classification of Men’s Competitive Gymnasts: A Field Study - Zaher Ashour; Hassan Daneshmandi; Hossein Fakoor Rashid (مجله علوم پزشکی صدرا)
Introduction: The Gymnastics Functional Measurement Tool is comprised of 10 tests. The purpose of this study was to investigate the relationship between the overall score on the gymnastics functional measurement tool and the technical skill class of competitive male gymnasts.Methods: This field design research was conducted on 25 boy gymnasts, aged 7 to 17, from Guilan province, who competed in a two-part gymnastics competition (floor exercise and vaulting). The sample was selected by a non-random sampling method. The results of the competition in the technical skill classification of the athletes were obtained with the coordination of the Guilan Province Gymnastics Federation and after one week of the competition and having enough time for physical recovery and intervention avoidance, a functional movement measurement test (GFMT) was taken for each participant on their usual training day and time and after proper warm-up. Pearson and Spearman correlation tests were used to check the relationship between variables. The data were analyzed using SPSS software, with a significance level of P≤0.05.Results: The correlation coefficient tests revealed a positive and significant relationship between the gymnastics functional measurement tool scores and the technical skill score of ground movements, as well as the overall technical score of the competition. There was no significant relationship between the gymnastics functional measurement tool scores and the vaulting technical skill score.Conclusion: It seems that the gymnastics functional measurement tool evaluation score, which assessed gymnasts’ technical skill, had an adequate level of accuracy.